Teachers' Perception Towards the Integration of Artificial Intelligence in the Teaching of Mathematics in Senior Secondary School - Asanre, Akorede Ayoola; Taiwo, Taiwo Oluwadayo; Odupe, Toyin Alaba (Jurnal Pendidikan Matematika dan Sains, 2024)
In many societies today, Artificial intelligence (AI) has developed into a disruptive force, and the system of education is only one example of how this technology is being used. Therefore, this study looked at the teachers' perceptions in terms of perception, attitude, and experience towards incorporating AI into mathematics education in senior secondary school in Remo, Ogun State, Nigeria. Three research questions were raised to gather data from the respondents. A descriptive survey research design was used in this study with a sample comprised of 60 respondents, with 30 teachers from private and public senior secondary schools each selected from 20 schools. The instrument used was the Teacher Perception Towards AI Questionnaire (TPTAQ) with a reliability coefficient of 0.77. The results revealed that the perceptive level of the teachers towards AI integration was found to be high in terms of perception, attitude, and experience, showing that teachers embrace the use of AI in mathematics education in schools. Therefore, educators are advised to be well-trained in the application of AI technology to mathematics education.